The Implementation of research-based Merdeka Belajar curriculum in Islamic religious education study programs in Indonesia - Afiful Ikhwan; Fina Kholij Zukhrufin; Moh. Subhan; Darliana Sormin; Uswatun Khasanah (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study aims to explain the research-based learning model, its implementation in the Islamic Education Philosophy course, its implications for students, and its primary focus on improving students' critical thinking skills, thereby encouraging them to actively build knowledge through literature analysis and field findings. This study employs a qualitative approach, focusing on a case study within the Islamic Religious Education Undergraduate Study Program at Universitas Muhammadiyah Ponorogo. Data collection techniques include interviews with lecturers and the head of study programs, observation of learning activities, documentation of RPS, Google Classroom, and publication of results to evaluate the implementation and effectiveness of research-based learning. Data validity testing involves triangulating sources, methods, and conducting member checks to ensure data credibility. Data analysis using the Miles, Huberman, and Saldana models involves condensation, data display, and conclusion. The research learning model for the Islamic Education Philosophy course consists of five steps: downloading 20 journals; creating a research model canvas (RMC) research guideline; collecting data, compiling research articles, and submitting articles; peer review and mind-mapping of research results; and publishing articles and evaluating lectures. The theoretical implications of the research-based learning model are the development of students' critical and analytical thinking skills. In contrast, the practical consequences include enhancing research and publication skills, as well as contributing to the advancement of Islamic education science. This study describes a learning model that enhances students' critical thinking skills in Islamic Education Philosophy by addressing philosophical challenges and traditional, monotonous learning methods. This model contributes to the development of Islamic education science and students' research skills.